Identification of Microalgae Isolates Using 18 S rRNA Markers and Testing Their Antioxidant Capacity - Ermavitalini, Dini; Rahmahana, Ratna Syifa'a; Saputro, Triono Bagus; Rizam, Bilqis Naura Safira; Purnobasuki, Hery; Ni'matuzahroh (Universitas Negeri Semarang, 2025)
Microalgae are photoautotrophic microorganisms that synthesize bioactive compounds, including antioxidant compounds. Exploratory research on microalgae with strong antioxidant capacity as free radical scavengers is interesting and important to do. This study aims to identify and evaluate the antioxidant capacity of microalgae. Water samples were diluted with multilevel dilution. Microalgae were isolated using the streak plate method, and four microalgae isolates were successfully cultivated in vitro. Identification was carried out by phylogenetic analysis based on 18S rRNA marker gene sequences, namely Chlorella vulgaris, Desmodesmus armatus, Dictyosphaerium ehrenbergianum, and Vitreochlamys incisa. Antioxidant capacity was evaluated using three methods, namely DPPH (2,2-diphenyl-1-picrylhydrazyl), ABTS (2,2'-azino-bis (3-ethylbenzothiazoline-6-sulfonate)), and FRAP (Ferric Reducing Antioxidant Power). IC50 as the concentration required to inhibit 50% of free radicals showed that methanol extract of C. vulgaris had a strong antioxidant capacity in the ABTS test with IC50 of 81.693 ppm and the highest in the DPPH test with IC50 of 297.451 ppm. In the FRAP test, the highest antioxidant capacity was in ethanol extract of D. ehrenbergianum isolate of 74.45 mg AAE/g. The D. armatus isolate had the lowest antioxidant capacity in the ABTS, DPPH, and FRAP tests.